Teacher’s and Young Learners’ Needs in English Teaching and Learning Environment - Pradnyana, Giri Tastra; Santosa, Made Hery; Saputra, I Nyoman Pasek Hadi (The Art of Teaching English as a Foreign Language (TATEFL), 2022)
The goal of this study was to analyze teachers’ obstacles in teaching English in SD Negeri 3 Banjar Jawa and students’ issues in the classroom from the teacher's perspective. The issues and solutions in teaching English to teachers were identified using a qualitative technique. The participant was interviewed using a Google Form. Based on the teacher's perspective, the results indicated that the teacher has two main problems, being that students have difficulties in learning vocabulary and pronunciation and that the teachers needed engaging learning material for the students. Teachers are encouraged to bring technology to the classroom to motivate the students during the teaching and learning process.